Análise da capacidade ao cisalhamento de paredes de contraventamento em alvenaria estrutural - Tinoco, Vinícius Navarro Varela (Universidade Federal de São Carlos, 2023)
Structural masonry systems are widely used in civil engineering due to the popularization of this construction method and potential savings. Several shear resistance equations are presented in the national and international normalization, and are used by structural engineers for analysis and design of this structures in the matter of lateral load structure resistance. It is necessary too to analyze and compare the different standards so that they can advance at the same pace as scientific knowledge, adding greater fidelity to the expected behavior, combining safety with economy. Therefore, it becomes essential to carry out a comparative study between the regulations and the most faithful predictions available of the behavior of the masonry structure responding to lateral loading that can, based on analysis, add to knowledge and design. Aiming at this issue, the present work seeks to present the main differences between the regulations for the resistant design of masonry structures, seeking to add, from the finite element study, to the prediction of the behavior of structural partially grouted masonry, under the design of different vertical regions between openings. For this, a parametric study was carried out based on what is most current in the literature regarding structural masonry modeling to form the database that will be used in the validation of this work. Among the five norms used, it was possible to perceive the following increasing order of resistant lateral load: Eurocode by diagonal compression (EN 1996-1-1, 2005); Canadian (CSA S304, 2014); Eurocode for slippage (new proposition of EN 1996-1-1); American (TMS 402/602, 2016); Australian (AS 3700, 2018) and Brazilian (NBR 16868-1, 2020), with the American being the closest to the modeling results and the reliable equation used. The flexo-compression was evaluated, with no significant difference in values between the standards. Based on the evaluation of other standards, a correction was also proposed to the Brazilian standard for the following factors to make it more conservative: net area of the masonry section; initial shear strength value; and decrease of the friction angle to be considered in the precompression portion. The proposal makes the standard more conservative and uses calculation factors that are already used in other standards.
Analysis of the shear capacity of structural masonry walls
Keywords: Alvenaria estrutural; Paredes de contraventamento; Modelos de elementos finitos; Normas técnicas; Forças horizontais; Structural masonry; Shear walls; Finite element models; Technical standards; Horizontal loads; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS